Pre-hospital Assessment of Large Vessel Occlusion Strokes: Implications for Modeling and Planning Stroke Systems of Care - Lima, Fabricio O.; Mont'Alverne, Francisco José Arruda; Bandeira, Diego; Nogueira, Raul G. (Frontiers in Neurology, 2019)
The social and financial burden of stroke is remarkable. Stroke is a leading cause of death and long-term disability worldwide. For several years, intravenous recombinant tissue plasminogen activator (IV rt-PA) remained as the only proven therapy for acute ischemic stroke. However, its benefit is hampered by a narrow therapeutic window and limited efficacy for large vessel occlusion (LVO) strokes. Recent trials of endovascular therapy (EVT) for LVO strokes have demonstrated improved patient outcomes when compared to treatment with medical treatment alone (with or without IV rt-PA). Thus, EVT has become a critical component of stroke care. As in IV rt-PA, time to treatment is a crucial factor with high impact on outcomes. Unlike IV rt-PA, EVT is only available at a limited number of centers. Considering the time sensitive benefit of reperfusion therapies of acute ischemic stroke, costs and logistics associated, it is recommended that regional systems of acute stroke care should be developed. These should include rapid identification of suspected stroke, centers that provide initial emergency care, including administration of IV rt-PA, and centers capable of performing endovascular stroke treatment with comprehensive periprocedural care to which rapid transport can be arranged when appropriate. In the prehospital setting, the development of scales easier and quicker to perform than the NIHSS yet with a maintained accuracy for detecting LVO strokes is of paramount importance. Several scales have been developed. On the other hand, the decision whether to transport to a primary stroke center or to a comprehensive stroke center is complex and far beyond the simple diagnosis of a large vessel occlusion. Ongoing studies will provide important answers to the best transfer strategy for acute stroke patients. At the same time, the development of new technologies to aid in real time the decision-making process will simplify the logistics of regional systems for acute stroke care and, likely improve patients’ outcomes through tailored selection of the most appropriate recanalization strategy and destination center.